Association Between Uremic Pruritus and Differential Leukocyte Counts Among Hemodialysis Patients in Ibn Sina Dialysis Center - Hiba M. Al-Darraji; Ismail Ibrahim Latif; Fatimah khazaal khamees Al-majmaie; Nabeel Khalid Al Wandi (Diyala Journal of Medicine, 2025)
Background: Pruritus is a common and bothersome symptom of chronic kidney disease (CKD). According to the most recent epidemiologic data, about 40% of patients with end-stage renal disease (ESRD) experience moderate to severe pruritus. The reason for uremic pruritus remains poorly understood, but recent studies suggest a strong association with the inflammatory process and elevated white blood cell (WBCs). Objectives: This study aims to investigate the correlation between uremic pruritus (UP) and differential leukocyte levels in patients with CKD undergoing dialysis (Hemodialysis patients), and to examine the potential role of inflammation in the severity of pruritus. Patients and Methods: A study was conducted at Ibn Sina Dialysis Center, Diyala Governorate, Iraq. The study involved 150 hemodialysis (HD) patients, divided into two groups: 75 patients with UP and 75 without UP. The control group consisted of 26 healthy individuals. Out of 226 HD patients at the Dialysis Center, those under 20 years old, as well as patients with hepatitis C or hepatitis B, were excluded. From each patient and control in this study, 3 ml of venous blood was collected before dialysis, placed in an ethylene diamine tetraacetic acid (EDTA) tube for leukocyte differential count, and analyzed at the educational laboratory of Baqubah Teaching Hospital. Results: The results showed that 33.8% of HD patients had uremic pruritus and had a significantly higher eosinophil level when compared with patients without UP and controls. While basophil and neutrophil showed no significant difference in patients with UP and without UP when compared with the control. When compared to patients without UP, HD patients with UP had higher lymphocyte counts; however, there was no discernible difference between the control group, hemodialysis patients with UP, and patients without UP. Conclusion: It was shown that eosinophils may play an essential role in the pathogenesis of UP by inducing and secreting materials that exacerbate its severity. Lymphocytes can also play a role in the pathogenesis of UP by secreting cytokines. Keywords: Uremic pruritus, Leukocytes. Hemodialysis, Diyala, Eosinophil.